The Impact of Family and Social Support During the First Six Months After Attempt for Smoking Cessation - Yalçın, Bektaş Murat; Ünal, Mustafa (My University, 2019)
Objective: The aim of the present study was to investigate the effect of family and social support on smoking cessation during the first sixmonths after the cessation attempt. Methods: The files of 312 patients who were admitted to the Smoking Cessation Outpatient Clinic ofFamily Medicine Department, Ondokuz Mayıs University Faculty of Medicine between January 2011 and January 2012 were reviewed andtheir socio-demographic data, smoking characteristics, Fagerström Nicotine Dependence Test (FNDT) score and treatment methods wererecorded. Participants were called in a five-minute structured interview and their quit rate was investigated. They were also evaluated forthe support they received from the family and social environment during the cessation period with a ten-point Likeert Scale (0 Never,10 Excellent) Findings: Of the cases, 190 (61%) were male and 122 (39%) were female. While the mean FNBT score of the group was5.1 1.7 , the package / year value was 22.3 18.7. Forty four out of 209 participants (21%) who were started medication (Varenicline orBupropion) and 23 out of 127 participants (%18%) who were started Nicotine Replacement Therapy (NRT) had been smoking for sixmonths. There was not a statistically significant difference between genders with regard to overall social and family support scores (male 41,3 15,3, female 44,4 16,0, t 1,495, p 0,136). According to a multivariate binary logistic regression model, overall social andfamily support score (OR 1,044), age (OR -1,038), and presence of another smoker family member (OR 0,501) were found asindependent factors on smoking cessation. Conclusion: Family and social support are important factors for both gender during making adecision for smoking cessation, during smoking cessation and after smoking cessation and detailed studies are needed.

Amaç: Bu araştırmada sigara bırakma denemesine karar verme ve sonraki ilk altı aylık dönemde sigara bırakma üzerine aile ve sosyalçevreden alınan desteğin etkisinin araştırılması hedeflenmiştir. Araç ve Yöntem: Ondokuz Mayıs Üniversitesi Tıp Fakültesi AileHekimliği Sigara Bıraktırma Polikliniği’ne Ocak 2011-Ocak 2012 tarihleri arasında başvuran 312 kişinin dosyaları taranarak kişilerinsosyodemografik verileri, sigara kullanma özellikleri, Fagerstrom Nikotin Bağımlılık Testi (FNBT) skoru ve aldıkları tedavi yöntemleri notedilmiştir. Bu kişiler telefonla aranarak beş dakikalık yapılandırılmış bir görüşme gerçekleştirilmiş ve sigarayı bırakma oranlarıaraştırılmıştır. Görüşmede ayrıca sigara bırakma aşamasında ve sigarayı bırakırken aileden ve sosyal çevreden aldıkları destek onlu birLikert Skala ile değerlendirilmiştir (0Hiç, 10Mükemmel). Bulgular: Çalışmaya alınanların 190’ı (% 61) erkek, 122’si (%39) kadındı.Grubun ortalama FNBT skoru 5,11,7 iken paket/yıl değeri 22,318,7 idi. İlaç (Vareniklin veya Bupropion) tedavisi başlanan 209katılımcının 44’ü (%21), Nikotin Replasman Tedavisi (NRT) başlanan 127 katılımcının 23’ü (%18) altı aydır sigara içmiyordu (x20,283,p0,868). Her iki cinsiyetin aldığı toplam sosyal destek ve aile desteği puanları birbirinden istatistiksel olarak anlamlı değildi (erkekler41,315,3, kadınlar 44,416,0, t1,495, p0,136). Multivariate binary logistic regression modeline göre toplam sosyal ve ailesel destekpuanı (OR 1,044), yaş (OR -1,038) ve sigara bağımlısının evinde başka birinin daha sigara içmemesi (OR -0,501) sigara bırakmaüzerinde bağımsız faktörler olarak bulunmuştur. Sonuç: Sigara bırakma kararı alma, bırakma esnasında ve bırakma sonrasında aile desteğive sosyal destek her iki cinsiyet için önemli bir faktördür ve bu konuda detaylı araştırmalara ihtiyaç vardır.
Sigara Bırakmada Aile Desteğinin ve Sosyal Desteğin İlk Altı Aylık Dönemdeki Etkisi